2021
DOI: 10.3390/pharmaceutics13122088
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Structure Determination of Sesquiterpenes from Neurolaena lobata and Their Antiproliferative, Cell Cycle Arrest-Inducing and Anti-Invasive Properties against Human Cervical Tumor Cells

Abstract: Seven new germacranolides (1–3, 5–8), among them a heterodimer (7), and known germacranolide (4), eudesmane (9) and isodaucane (10) sesquiterpenes were isolated from the aerial parts of Neurolaena lobata. Their structures were determined by using a combination of different spectroscopic methods, including HR-ESIMS and 1D and 2D NMR techniques supported by DFT-NMR calculations. The enantiomeric purity of the new compounds was investigated by chiral HPLC analysis, while their absolute configurations were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Although NOE correlations work well in smaller rings, for flexible systems or macrolides one should be careful with the interpretations to avoid misassignments [ 24 , 50 , 51 ]. Therefore, we tested a large number of available DFT NMR methods, developed parameters for two combinations and augmented the NMR studies with TDDFT-ECD calculations to verify the stereochemistry of 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although NOE correlations work well in smaller rings, for flexible systems or macrolides one should be careful with the interpretations to avoid misassignments [ 24 , 50 , 51 ]. Therefore, we tested a large number of available DFT NMR methods, developed parameters for two combinations and augmented the NMR studies with TDDFT-ECD calculations to verify the stereochemistry of 1 .…”
Section: Resultsmentioning
confidence: 99%
“…It is a rich source of SLs; previously 24 sesquiterpenes, among them 22 SLs having germacranolide, seco -germacranolide, furanoheliangolide and eudesmanolide skeletons were isolated from the aerial parts of the plant. Several of them possessed remarkable antiproliferative and anti-inflammatory activities [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Probably plants are the most well-known source of molecules with demonstrated anticancer therapeutic properties. Another set of papers of this Special Issue have investigated the antitumoral properties of plant extracts and plant-derived compounds, revealing interesting antiproliferative and/or pro-apoptotic activities in vitro [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. In addition, Huang and coworkers have shown that Ceylon olive leaf extract and its phytochemicals, such as mearnsetin, displayed potent antimelanogenesis effects in a zebrafish model [ 19 ].…”
mentioning
confidence: 99%